The Multifaceted Effects of Alpha1-Antitrypsin on Neutrophil Functions - Janciauskiene, Sabina; Wrenger, Sabine; Immenschuh, Stephan; Olejnicka, Beata; Greulich, Timm; Welte, Tobias; Chorostowska-Wynimko, Joanna (Frontiers in Pharmacology, 2018)
Neutrophils are the predominant immune cells in human blood possessing heterogeneity, plasticity and functional diversity. The activation and recruitment of neutrophils into inflamed tissue in response to stimuli are tightly regulated processes. Alpha-1-antitrypsin (AAT), an acute phase protein, is one of the potent regulators of neutrophil activation via both -protease inhibitory and non-inhibitory functions. This review summarises our current understanding of the effects of AAT on neutrophils, illustrating the interplay between AAT and the key effector functions of neutrophils.